A Study of the Mechanism of Environmental Education and Awe on Tourists' Pro‐Environmental Behavior - Yin, Chengqiang; Li, Wenming; Yang, Xingzhu (The international journal of tourism research, 2025)
ABSTRACT This study investigates how amalgamation of environmental education and awe influences pro‐environmental behavior through the formulation of two models: Model A, which focuses on environmental education, and Model B, which emphasizes awe. Using 300 survey responses and PLS‐SEM, this study assesses these models in China's Jinggangshan Scenic Area. It finds that these two approaches effectively promote pro‐environmental behaviors among tourists by integrating emotional engagement with environmental education. Model B, dominated by awe, exhibits higher explanatory power. Awe and the “Need for Accommodation” can directly foster pro‐environmental behaviors among tourists, as well as through the intermediary function of environmental education. The “Appraisal of Vastness” largely exerts a direct impact through awe and the sequential process of environmental education. This study provides a cognitive‐behavioral framework that incorporates environmental education and sensations of awe for enhanced elucidation. This study's findings demonstrate that hard/passive environmental education holds substantial importance in military historical sites and offers practical assistance.